2010
DOI: 10.1021/jf101417w
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Oxytetracycline to Bovine Serum Albumin: Spectroscopic and Molecular Modeling Investigations

Abstract: The residue of the widely used veterinary drug oxytetracycline (OTC) in the environment (e.g., animal food, soils, surface water, and groundwater) is potentially harmful. Knowledge of its binding to proteins contributes to the understanding of its toxicity in vivo. This work establishes the binding mode of OTC with bovine serum albumin (BSA) under physiological conditions by spectroscopic methods and molecular modeling techniques. The inner filter effect was eliminated to get accurate data (binding parameters)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
90
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 210 publications
(95 citation statements)
references
References 45 publications
4
90
1
Order By: Relevance
“…The value of K sv was in the order: CA N LUN QU N TA. All the quenching rate constants (k q ) were far greater than the expected maximum dynamic quenching constant (2.0 × 10 10 L·mol − 1 ·s − 1 ), therefore, the fluorescence quenching process of BSA at investigated concentrations of flavonoids might be mainly governed by a static quenching mechanism rather than a dynamic quenching process (Chi, Liu, Teng, Fang, & Gao, 2010).…”
Section: Quenching Of Bsa Fluorescence By Qu Lu Ta and Camentioning
confidence: 99%
“…The value of K sv was in the order: CA N LUN QU N TA. All the quenching rate constants (k q ) were far greater than the expected maximum dynamic quenching constant (2.0 × 10 10 L·mol − 1 ·s − 1 ), therefore, the fluorescence quenching process of BSA at investigated concentrations of flavonoids might be mainly governed by a static quenching mechanism rather than a dynamic quenching process (Chi, Liu, Teng, Fang, & Gao, 2010).…”
Section: Quenching Of Bsa Fluorescence By Qu Lu Ta and Camentioning
confidence: 99%
“…The binding sites of endogenous or exogenous ligands to BSA/HSA may be in these domains, and the principal regions of the binding sites on proteins are located in the hydrophobic cavities in subdomains IIA or IIIA. Moreover, many ligands could bind specifically to serum albumins, such as, phenylbutazone and warfarin for site I, IB and flufenamic acid for site II, and DIG for site III [22]. In order to ascertain the binding sites on HSA and BSA for ergosterol, the displacement experiments were performed using the site probes, which was phenylbutazone, IB and DIG.…”
Section: Mechanisms Of Fluorescence Quenchingmentioning
confidence: 99%
“…19 Moreover, the three Tyr residues in the C-terminus of α-synuclein play a crucial role in fibril formation in vitro. 20 Indeed, this was completely inhibited when the three Tyr residues were replaced with Ala. 20 Importantly, it has been recently shown that binding of ceftriaxone to bovine serum albumin (BSA) is sufficient to perturb the environment in the proximity of Tyr residues, making the latter one from nonpolar to slightly polar, with a slight increase of the hydrophilicity around Tyr residues. 21 By analogy, we may speculate that in our experimental model, the binding of ceftriaxone to α-synuclein may have tempered the hydrophobicity related to Tyr residues in the C-terminus of α-synuclein.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…While the hydrophobic NAC region of α-synuclein is the most important site in the formation of amyloid-like fibrils, some of the residues present in the hydrophilic tail of the C-terminus, such as Tyr125, Tyr133, and Tyr136, are predicted to play a crucial role in fibril formation. 20 Thus, the binding to this region of a putative inhibitor should affect α-synuclein aggregation and prevent intracellular accumulation of misfolded protein. Accordingly, although the protein topology presents a micelle binding state, the unfolded region of the protein on the hydrophilic tail (Asp98-Ala140) can be well suited as a docking target ( Figure 6).…”
Section: ■ Results and Discussionmentioning
confidence: 99%